Dynamic Project Interdependencies (PI) in Optimizing Project Portfolio Management (PPM) - Rahayu S. Arifin; Setyo Sarwanto Moersidik; Edhi Tri Budi Soesilo; Djoko M. Hartono; Yusuf Latief (International Journal of Technology, 2015)
Many researchers assess the tools and techniques to optimize the project portfolio management. Most of those tools treat each project within a portfolio as an independent entity. Starting in 2010 onwards, many researchers considered the importance of Project Interdependencies (PI) in defining the Project Portfolio (PP); however, those researchers treated PI as a static condition. Organization strategy has dynamic characteristics caused by internal dynamics as well as external forces. Since the PP is a bridge between organization strategy and the program/project, the PP has to have a dynamic ability, in order to support the organizational strategy dynamics. This research applies an interactive approach using System Dynamics (SD) modelling to represent the PI dynamics as well as a project selection tool/technique within a project portfolio. A case study was conducted with the Bandung Urban Waterworks (PDAM Tirtawening). The outcomes of this research suggest that the model developed by the SD approach is: 1) one of the tools and techniques is to specify the PI dynamics; 2) to determine project priority in order to optimize the project portfolio. SD approach has the ability to challenge an organization’s perception of their project portfolio interdependencies and to enhance strategic decision making capabilities. PI on this research is driven by project outcomes. PI that driven by other reasons, such as by market, resources, knowledge, etc., should be leveraged more, to figure out a complete picture of the PI importance within Project Portfolio Management (PPM).